TRADISI SUMBANGAN PADA PESTA PERKAWINAN (Benang tipis antara respon resiprositas, adat - Hutang) - Isro Puad; Sasmita Nur Faradisa; Ahmad Muzayyin (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2024)
Traditions in society are very different and these activities are not just traditions but have become customs. Even for followers of the Islamic religion, these customs are no longer pure customs but have been decorated with strong religious values. So the sacred value of these traditions is completely different. One of the traditions that already has religious values ​​is Selametan wedding or walimah al ursy. Marriage itself is a life partnership between a man and a woman which is formally confirmed by law, namely juridical and mostly also religious according to the purposes of husband and wife and the law, and is carried out for the duration of his life according to the institution of marriage. To carry out this wedding celebration, relatives and neighbors usually flock to help or contribute in terms of thoughts, energy and logistics. The characteristics of wedding donations are a number of funds and goods in the form of money, gifts and basic necessities such as rice, sugar, cakes and others. Initially, these donations were mutually voluntary, but quite a few people found that the donated items became a deposit or debt. The research method used is normative Islamic law, the data source consists of primary legal materials, secondary legal materials and tertiary legal materials. And in writing this scientific work it can be concluded that the tradition of donation in the Situbondo community is not purely in the form of giving or alms but rather tends towards debt. Because every time you give a donation, it will be recorded and at a later date it will be returned according to the records. Meanwhile, in Islamic law, helping in terms of donating is permissible and even prescribed. However, whether it is called a debt or not depends on the agreement at the beginning.